Comparison of paracetamol and diclofenac as prophylactic analgesics during hysterosalpingography in Bayelsa State, South-South Nigeria: a randomized controlled trial - Kiridi, Enefia Kelvin; Oriji, Peter Chibuzor; Ugwoegbu, Johnpatrick Uchenna; Ubom, Akaninyene Eseme; Abasi, Isaac Joel (International Journal of Scientific Reports, 2022)
Background: Hysterosalpingography is the investigative modality of choice for the evaluation of the uterine cavity, fallopian tubes, and adjacent peritoneal cavity. Objective were to compare the effectiveness of paracetamol and diclofenac in pain relief during hysterosalpingography. Methods: This trial was conducted at the radiology departments and infertility clinics of the Federal Medical Centre, Yenagoa, and Niger Delta University Teaching Hospital, Okolobiri, both in Bayelsa State, Nigeria, from June 2021-March, 2022, and 380 infertile women undergoing hysterosalpingography were equally randomised into two groups. Group I received paracetamol, while group II received diclofenac prior to the procedure. Data were analysed using statistical product and service solutions for Windows® version 25. Student’s t-test was used to compare sample means, and the Chi-square test was used to compare the proportions. Results: The women experienced the least pain during insertion of speculum, with an overall mean pain score at this step of 0.8±0.9, while the most painful step was instillation of contrast, the overall mean pain score at this step being 4.3±1.9. While 38, 20.0%, women in the paracetamol group expressed severe pain during contrast instillation, only 14, 7.4%, women in the diclofenac group expressed severe pain at this step, and this was statistically significant (ꭓ2=22.05; p=0.001). The mean pain scores at all steps of the procedure were significantly higher in the paracetamol group than in the diclofenac group (p≤0.005). Conclusions: Compared to paracetamol, diclofenac is a more effective analgesic for pain relief during hysterosalpingography.